(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article examines the role of lending for environmentally sustainable projects in advancing the goals of sustainable development. It explores the economic, financial, environmental, and social benefits of green financing, as well as the associated risks that may undermine its effectiveness. The study highlights the importance of green finance instruments, including loans, bonds, and investment funds, in facilitating the transition to a green economy while maintaining financial stability and promoting long-term economic resilience.